THE IMPLICATION OF MORAL VALUES FOUND IN THE LYRICS ISLAMIC POP SONG ON TEACHING ENGLISH AS FOREIGN LANGUAGE (TEFL) - Jumaini Mulia Wati (Esteem Journal of English Education Study Programme, 2022)
The purpose of the analytical research conducted by researcher was to find moral values in the lyrics of the best song of Sami Yusuf and the theoretical implication of Sami Yusuf's song for Teaching English as Foreign Language (TEFL). To find out the moral values contained in the song, the researcher examines each song's lyrics that contain educational moral values by applying several theories such as: Linda and Richard Moral Value, Webster and Buzan. This type of research is descriptive analysis research, where this research is carried out by analysing and describing the object of research which is supported by expert theories and various library sources. The research method used in this study is descriptive qualitative method. The sources of data were seven songs from the best song of Sami Yusuf. Method of collecting the data is triangulation: lyrics, interview and book review. The data of this study were analysed by following steps: reading tenth lyrics from the album, understanding the contents and analysing the moral values in the lyrics of songs. After analysing there were ten moral values contained in the lyrics of the song, it could build the good character for student and for the theoretical implication for TEFL could be concluded that moral values could be taught through songs.